Metastatic lesions of atrial myxoma. A pathologist can clinch them all. Issue 3 (30th March 2020) - Rajeshwari, Madhu; Subramanian, Priyadarsani; Suri, Vaishali; Nambirajan, Aruna; Garg, Ajay; Vibha, Deepti; Phalak, Manoj; Sharma, Mehar Chand
Abstract : Atrial myxomas are the most common primary benign cardiac tumors. The embolization of tumor particles is not infrequent, and in nearly half of them, the cerebral arteries are affected, usually leading to embolic ischemic stroke. Formation of intracranial aneurysms, development of parenchymal brain metastasis, and intracerebral hemorrhage due to ruptured aneurysms are rarer. Diagnosis of such lesions in a previously undiagnosed case of myxoma may be challenging for a pathologist. Herein, we present two patients of cardiac myxoma with varied neurological manifestations and their pathological findings.